Mangrove damage level in the waters of Berakit Village, Bintan Island, Indonesia - Susiana Susiana; Mario Putra Suhana (Sekolah Tinggi Ilmu Pertanian Wuna, 2019)
Mangrove forest or better known as mangrove forest is an ecosystem found in coastal waters and has an important ecological and economic role. This study aims to measure and determine the health status of mangrove forests that grow in the waters of Berakit, Bintan based on the level of tree density. The study was conducted in August to November 2019 which was conducted at twenty station points spread from the mainland to the coastal waters of Berakit. Field data collection was performed using the quadratic transect line method, 10x10 m2 plot was made along the transect line to measure the diameter of the tree at breast height (DBH) which has a trunk circumference for each mangrove tree at breast height of about 1.3 m. Mangrove health status based on the level of density of mangrove trees is included in the criteria of Good with Very Solid category. Rhizophora apiculata is a species of mangrove that grows well and has an important role in the waters of Berakit, Bintan island.